The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/1710-1492-10-13
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight, gestational age, fetal growth and childhood asthma hospitalization

Abstract: BackgroundChildhood asthma may have a fetal origin through fetal growth and development of the immunocompetence or respiratory organs.ObjectiveWe examined to which extent short gestational age, low birth weight and fetal growth restriction were associated with an increased risk of asthma hospitalization in childhood.MethodsWe undertook a cohort study based on several national registers in Denmark, Sweden and Finland. We included all live singleton born children in Denmark during 1979-2005 (N = 1,538,093), in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 55 publications
0
39
1
Order By: Relevance
“…In addition, various studies have detected positive correlations between in utero PCB exposure, which is frequently associated with the consumption of fish, and the risk of a low birth weight [48,49]. We did not detect a significant relationship between birth weight and PCB in the present study (data not shown); however, some studies have indicated that a link exists between low birth weight and childhood allergies [50,51]. Furthermore, it remains unclear which types of PCB congeners and PCB homologs are associated with childhood conditions, such as allergies.…”
Section: Primercontrasting
confidence: 80%
“…In addition, various studies have detected positive correlations between in utero PCB exposure, which is frequently associated with the consumption of fish, and the risk of a low birth weight [48,49]. We did not detect a significant relationship between birth weight and PCB in the present study (data not shown); however, some studies have indicated that a link exists between low birth weight and childhood allergies [50,51]. Furthermore, it remains unclear which types of PCB congeners and PCB homologs are associated with childhood conditions, such as allergies.…”
Section: Primercontrasting
confidence: 80%
“…Indeed, by using a propensity score approach to control for confounders, it has been showed that birth weight is not associated with the risk of asthma during the first six years of life 68 . In addition, after considering the maternal smoking status in pregnancy 27 and gestational age 26,69 , the estimated association size between lower birth weight with asthma is much reduced. Therefore, our MR results are consistent with these observational studies that properly controlled for confounding effects, providing additional evidence supporting that birth weight may not be directly associated with adult asthma.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence rate varies among countries, the increase pattern usually observed in many Low- and Middle-Income counties, especially in Eastern Europe and Latin American, as well as Northern African countries [4, 5]. The cause of asthma remains unclear and current research paints a complex picture [6, 7].…”
Section: Introductionmentioning
confidence: 99%